Surgical Correction of Dissecting Aortic Aneurysms Combined with Coronary Bypass Surgery in Marfan Syndrome - Ihor I. Zhekov; Vitalii I. Kravchenko; Oleh I. Sarhosh; Iryna A. Osadovska; Anatoliy V. Rudenko (Ukrainian Journal of Cardiovascular Surgery, 2023)
Introduction. The cohort of patients with aortic dissection and coronary heart disease is very complex, and their surgical treatment remains a relevant and debatable topic to this day. The presence of Marfan syndrome (MS) makes this difficult group of patients even more challenging. In this work, we present our own seven-year experience with the analysis of the impact of MS on the results of surgical treatment of patients with dissecting aortic aneurysm and coronary heart disease.Materials and methods. Nineteen consecutive cases of dissection of the aorta combined with lesions of the coronary arteries were analyzed. All the patients were operated at the premises of the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine from 2013 to 2022. Among them, 15 operations (78.9%) were performed for type A acute dissection of the aorta, 4 (21.1%) for type A chronic dissection of the aorta. Of the 19 operated patients, 5 (26.3%) had a diagnosed MS, 14 (73.7%) were the control group of patients with aortic dissection correction and aortocoronary bypass without MS.Results. A comparative analysis of two groups of patients showed more profound structural changes of the aortic wall especially with MS, which may affect the technical features of surgical intervention in this cohort of patients. Analysis of the mean time of perfusion, aortic clamping and intraoperative blood loss showed that the above indicators were not significantly different in both groups (p > 0.05). Indicators such as length of stay in the intensive care unit, length of stay on a ventilator, and the postoperative level of creatine phosphokinase-MB also were not significantly different in the observed groups.Discussion. In our study, we evaluated the effect of the presence of MS on the results of surgical correction of aortic dissection and coronary artery bypass grafting. According to the results of our study, it can be stated that MS does not significantly affect the results of surgical treatment, provided that careful approach to planning the operation is employed, and all available intraoperative methods that reduce the risk of postoperative complications are used.Conclusions. MS significantly accelerates the formation of aortic aneurysm, and also makes it more dangerous in the occurrence of acute dissection. In the group of patients with MS, damage to coronary arteries in most cases was associated with their involvement in the process of dissection, and only in some cases with atherosclerotic lesions. The use of all methods of bleeding prevention, as well as myocardial protection, allows to perform surgery in patients with MS with minimal risk.